Innovating Singapore’s chicken rice - CRAMA, Pascale (Institutional Knowledge at Singapore Management University, 2021)
"This case is set in November 2020. Lao Hung Jia (LHJ) was a progressive chicken rice hawker stall that had embraced digital transformation and open innovation from e-retailing, e-payment, e-distribution to e-marketing. Even though these digital transformation initiatives had helped LHJ improve its customer service, productivity had remained an issue, especially when 50 percent of a hawker’s work was spent on food preparation. CK Ng, the son of the founder of LHJ, reached out to the Food Innovation and Resource Centre (FIRC) at Singapore Polytechnic to conduct R&D to develop pre-mixed and pre-packaged sauces so that cooking chicken rice could be simplified. When the R&D at the FIRC was completed, Ng went to Sin Hwa Dee, a local sauce and paste manufacturer, to further develop and batch manufacture these three sauces, namely, the chicken stock, soya sauce and chilli sauce. Sin Hwa Dee was able to replicate the chicken stock and soya sauce, but it could not do so with the chilli sauce as the food retort production method used had altered the taste, colour and texture of the chilli sauce. Ng did not want LHJ to remain as a single chicken rice hawker stall. He had envisioned a LHJ franchise and dreamed about serving LHJ’s chicken rice in vending machines or unmanned stalls so that more people in Singapore and abroad could savour the dish. But all these plans were dependent on getting the pre-mixed and pre-packaged chilli sauce right – without it, many Singaporeans would agree that the chicken rice was ‘incomplete’. What should Ng do to make his dreams for LHJ a reality? Students will be able to 1) apply concepts of managing change, 2) develop a growth mindset, 3) evaluate how to manage multi-generational stakeholders, and 4) apply the concepts of open innovation."